National identity and the Anglo-Scottish borderlands, 1552-1652 - Schultz, Jenna M. (Studies in early modern cultural, political and social history, 2019)
A detailed examination of the March system - the special administrative arrangements which applied on both sides of the border - how it was applied and how it evolved as national political circumstances changed.